2012
DOI: 10.5152/akd.2012.034
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of aortic knob width with cardio-ankle vascular stiffness index and its value in diagnosis of subclinical atherosclerosis in hypertensive patients: a study on diagnostic accuracy

Abstract: Objective: The aim of our study was to determine the usefulness of the aortic knob width (AKW) in the assessment of subclinical atherosclerosis in hypertensive patients. Methods: In this study on diagnostic accuracy, 374 consecutive hypertensive patients with at least one cardiovascular risk factor were enrolled. AKW was measured on chest X-ray. Cardio-ankle vascular index (CAVI) was measured by VaSera-1000 CAVI instrument. The diagnostic value of AKW was assessed using ROC analysis. Results: There was a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 21 publications
1
23
0
1
Order By: Relevance
“…A significant doseresponse relationship between aortic knob width and AHI was observed. Second, there was a significant correlation between aortic knob width and the arterial stiffness parameter, CAVI, which is consistent with the report of another study including 374 patients with hypertension 10) . Third, multivariate regression analysis revealed that in patients with OSA, AHI was associated with aortic knob width independent of CAVI.…”
Section: Resultssupporting
confidence: 90%
“…A significant doseresponse relationship between aortic knob width and AHI was observed. Second, there was a significant correlation between aortic knob width and the arterial stiffness parameter, CAVI, which is consistent with the report of another study including 374 patients with hypertension 10) . Third, multivariate regression analysis revealed that in patients with OSA, AHI was associated with aortic knob width independent of CAVI.…”
Section: Resultssupporting
confidence: 90%
“…reported that a cut‐off level of 8.81 for CAVI yielded maximal sensitivity and specificity for coronary artery disease . We therefore defined increased arterial stiffness as abnormal CAVI (≥9), as was done in a previous study …”
Section: Methodsmentioning
confidence: 99%
“…15 We therefore defined increased arterial stiffness as abnormal CAVI (≥9), as was done in a previous study. 16…”
Section: Measurementsmentioning
confidence: 99%
“…Abnormal CAVI represents subclinical atherosclerosis. ba-PWV ≥ 17.5 m/sec was considered abnormal [ 39 , 40 ]. For the study, the higher obtained CAVI and ba-PWV were considered.…”
Section: Measurementsmentioning
confidence: 99%